Elevated expression of the toll like receptors 2 and 4 in obese individuals: its significance for obesity-induced inflammation - Ahmad Rasheed; Al-Mass Anfal; Atizado Valerie; Al-Hubail Asma; Al-Ghimlas Fahad; Al-Arouj Monira; Bennakhi Abdullah; Dermime Said; Behbehani Kazem (BMC, 2012)
Abstract Background Expression profile of the toll like receptors (TLRs) on PBMCs is central to the regulation of proinflammatory markers. An imbalance in the TLRs expression may lead to several types of inflammatory disorders. Furthermore, the dynamic regulation of inflammatory activity and associated impaired production of cytokines by peripheral blood mononuclear cells (PBMCs) in obese individulas remain poorly understood. Therefore, we determined the perturbation in TLRs (TLR2 and TLR4), their adaptor proteins (MyD88, IRAK1 and TRAF6) expression in PBMCs/subcutaneous adipose tissue (AT) as well as inflammatory cytokines changes in obese individuals. Methods mRNA expression levels of TLR2, TLR4, IL-6, TNF-α and adaptor proteins were determined by RT-PCR. TLR2, TLR4 and adaptor proteins expression in AT was determined by immunohistochemistry. Results Obese and overweight individuals showed significantly increased expression of TLR2, TLR4 and MyD88 in both PBMCs and AT as compared with lean individuals (P < 0.05). Interestingly, we found a remarkably higher expression of TLRs in obese and overweight individuals with type 2 diabetes (P < 0.05). Increased expression of TLR2, TLR4, MyD88 and IRAK1 correlated with body mass index (BMI) (TLR2: r = 0.91; TLR4: r = 0.88, P <0.0001; MyD88: r = 0.95, P < 0.0001; IRAK1 r = 0.78, P < 0.002). TLRs' expression was also correlated with fasting blood glucose (FBG) (TLR2: r = 0.61, P < 0.002; TLR4: r = 0.52, P < 0.01) and glycated haemoglobin (HbA1c) ( TLR2: r = 0.44, P <0.03; TLR4: r = 0.48, P < 0.03). Transcript levels of IL-6 and TNF-α were highly elevated in obese subjects compared to lean subjects. There was a strong association of TLRs' expression in PBMCs with TNF-α (TLR2: r = 0.92; TLR4: r = 0.92; P < 0.0001) and IL-6 (TLR2: r = 0.91, P < 0.0001; TLR4: r = 0.81; P < 0.001). Similarly adaptor proteins were significantly correlated with TNF-α (MyD88: r = 0.9, P < 0.0001; IRAK1: r = 0.86; P < 0.0002) and IL-6 (MyD88: r = 0.91, P < 0.0001; IRAK1: 0.77; P < 0.002). Conclusions TLRs and adapter proteins were overexpressed in PBMCs from obese subjects, which correlated with increased expression of TNF-α and IL-6. This association may explain a potential pathophysiological link between obesity and inflammation leading to insulin resistance.